2009
DOI: 10.4049/jimmunol.0803192
|View full text |Cite
|
Sign up to set email alerts
|

A Novel and Critical Role for Tyrosine 663 in Platelet Endothelial Cell Adhesion Molecule-1 Trafficking and Transendothelial Migration

Abstract: Platelet/endothelial cell adhesion molecule-1 (PECAM/CD31) is required for leukocyte transendothelial migration (TEM) under most inflammatory conditions. A critical pool of PECAM resides in the lateral border recycling compartment (LBRC). During TEM membrane from the LBRC is redirected to surround the leukocyte and this targeted recycling per se is required for TEM. The cytoplasmic domain of PECAM contains two tyrosine residues that have been implicated in PECAM signaling in other cells, but never examined in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 31 publications
(59 reference statements)
1
58
0
Order By: Relevance
“…2 Platelet/endothelial cell adhesion molecule 1 (PECAM-1) expressed in the EC plasma membrane is also critically involved in the mechanism of PMN transmigration. 5,6 Based on the key roles of both ICAM-1 and PECAM-1, a fundamental question is whether these adhesive proteins cooperate in the mechanism of PMN transmigration.…”
Section: Introductionmentioning
confidence: 99%
“…2 Platelet/endothelial cell adhesion molecule 1 (PECAM-1) expressed in the EC plasma membrane is also critically involved in the mechanism of PMN transmigration. 5,6 Based on the key roles of both ICAM-1 and PECAM-1, a fundamental question is whether these adhesive proteins cooperate in the mechanism of PMN transmigration.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, signaling mediated by PECAM-1 cytoplasmic ITIMs has been suggested to have a role in maintaining the vascular barrier because PECAM-1 expression has been reported to modulate -catenin phosphorylation and enhance vascular barrier stability through ITIM-mediated recruitment of SHP-2 (Biswas et al, 2006). Two other groups, however, found that ITIM-mediated recruitment of SHP-2 by endothelial cell PECAM-1 is not required for leukocyte transmigration through cell monolayers (Dasgupta et al, 2009;O'Brien et al, 2003), a process that involves the coordinated opening and closing of cell-cell junctions, which is very similar to the process occurring during regulation of vascular permeability. Finally, a role for raft-localized PECAM-1 is suggested by a report that PECAM-1 modulates signaling from the sphingosine-1-phosphate (S1P) receptor (Gratzinger et al, 2003) -a G-proteincoupled receptor that promotes barrier protection by enhancing junctional assembly via signaling in lipid rafts (Komarova et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Differences in the rate at which membrane proteins transit through the LBRC could also potentially affect their distribution on the surface versus LBRC. In a previous study, we showed that substitution of phenylalanine for tyrosine at position 663 in the cytoplasmic tail of PECAM decreases the efficiency of trafficking of PECAM into and out of the LBRC (and hence of targeted recycling required for leukocyte transmigration), but does not totally eliminate it (Dasgupta et al, 2009). During the constitutive recycling assays performed in our previous study, endothelial cells were exposed to antibody for 1 hour, which was sufficient time to saturate native PECAM, but might not have been enough time for a slowly recycling mutant.…”
Section: Discussionmentioning
confidence: 94%
“…We hoped that understanding how PECAM entered the LBRC would provide clues to how other components enter. Previous studies have demonstrated that mutation of tyrosine 663 in the PECAM cytoplasmic tail to phenylalanine interferes with the efficient movement of PECAM between the endothelial cell border and the LBRC (Dasgupta et al, 2009). However, standard signaling functions of PECAM were not altered (Dasgupta et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation